Tax Compliance: Sanction and Awareness Perspective of Motor and Car Owners in Indonesia - Mas Nur Mukmin; Siti Zuwariah; Indra Cahya Kusuma (Indonesian Journal of Social Research (IJSR), 2020)
The low awareness of motor vehicle taxpayers in Indonesia is in contrast to the motor vehicle tax revenue in the Bogor regency, which always exceeds the target. This study aims to reveal this phenomenon by involving the awareness variable and tax sanctions on taxpayer compliance. This study uses quantitative methods to 400 motor vehicle taxpayers. Research shows that tax awareness and sanctions have a significant effect on taxpayer compliance. This research has also succeeded in revealing that the determination of the target of motor vehicle tax revenue in the Bogor regency is appropriate.